Posted by **farook** on Sunday, April 24, 2011 at 2:20pm.

Find the Laplace transform by using the theorem of L{f(t-a)H(t-a)}=(e^-as)F(s)

L{(e^4t)H(t-10)}

## Answer This Question

## Related Questions

- calc 2 - (last one) ... Let f(t) be a function defined for all values of t. The ...
- Calc2 - Let f(t) be a function defined for all values of t. The Laplace ...
- Calculus - Solve the differential equation by using Laplace transforms. Find the...
- Differential Equations - Use the Laplace Transform to solve this initial value ...
- calculus - Solve the DE by using the Laplace transform: x''+x=cos(3t), x(0)=x'(0...
- Math - Using the table Laplace transform, determine the function f (t) of the ...
- Calculus - Find the Laplace transform of: f(t)=t-2e^(3t)
- Calculus - Find the inverse Laplace transform of: F(s)=3/(s-4)
- Calculus-HELP!!! - Find the inverse Laplace transform of: F(s)=2/s^4
- Calculus-HELP!!! - Find the Laplace transform of: f(t) = cos^(2)(2t)

More Related Questions